Modeling of oxygen incorporation in Th, ThC, and ThN by density functional theory calculations - Perez Daroca, Diego Raul (2017)
Oxygen incorporation in nuclear fuel materials is an important issue deserving investigation due to its influence on thermophysical and structural properties. Even if there has been a renewed interest in thorium and thorium compounds in the last years, there is still not much research done on this topic. In this work, we study, by means of density functional theory calculations, the incorporation of oxygen in Th, ThC, and ThN. We analyze the electronic structure finding a characteristic peak to be attributed to oxygen incorporation. We also calculate incorporation and solution energies and obtain migration energies of oxygen through different paths finding that migration through vacancy sites is more energetically favorable than through interstitial ones.